Local allergic rhinitis: mechanisms, diagnosis and relevance for occupational rhinitis. Issue 2 (April 2015) - Gómez, Francisca; Rondón, Carmen; Salas, María; Campo, Paloma
Abstract : Purpose of review: Local allergic rhinitis (LAR) is a new form of allergic rhinitis that has caused a growing interest. The possibility of an occupational equivalent (occupational rhinitis) has not been yet explored. The purpose of this review is to summarize the most relevant and recent scientific evidence on LAR and occupational rhinitis. Recent findings: LAR is a prevalent entity well differentiated from allergic rhinitis, affecting patients from different countries, ethnic groups and ages. Occupational rhinitis appears earlier and more frequently than occupational asthma, especially for high molecular weight substances. Diagnosis of LAR is based on nasal allergen provocation test and/or detection of nasal specific IgE, and other techniques such as basophil activation test may support the diagnosis. Skin prick tests and immunological determinations are of limited use for diagnosis of occupational rhinitis caused by low molecular weight agents. Performance of nasal allergen provocation test for confirming diagnosis of occupational rhinitis is strongly recommended. Uncommon allergens should also be investigated. Summary: The possibility of a local occupational rhinitis should be considered in workers with a clear history of occupational rhinitis and negative immunological test, especially in the case of high molecular weight allergens